English and French Teachers’ Assessment Practices in the Ukrainian Context: Understanding Language Assessment Literacy Needs Across Two Languages - Olga Ukrayinska (Education Sciences)
This paper explores assessment practices of teachers of English and French as a second language in the Ukrainian educational context with the aim of shaping the language assessment literacy (LAL) construct for teaching it to pre-service teachers. Seventy Ukrainian teachers completed a questionnaire designed to study their assessments that underpin their LAL. Analyses of the data confirmed the following: (1) teachers of English articulated a greater need for training in language testing and assessment, (2) teachers of English and French differ in the task formats they use, and (3) teachers of English and French assign different weight to various assessment criteria. These findings suggest that differences in assessment practices reflect cultural traditions in language pedagogies. Moreover, teachers’ assessments reflect the content of textbooks and international proficiency tests that they use for teaching purposes.